2018
DOI: 10.1541/ieejjia.7.298
|View full text |Cite
|
Sign up to set email alerts
|

Iron Loss and Hysteretic Properties under PWM Inverter Excitation at High Ambient Temperatures

Abstract: We experimentally and numerically investigate the magnetic properties of magnetic materials excited by sinusoidal and pulse width modulation (PWM) inverter input at high ambient and room temperatures. We show that the iron losses under sinusoidal and PWM inverter excitations decrease with an increase in temperature. It is found that the temperature dependency of iron loss properties is related not only to major loop but also to minor loops. Furthermore, we derive the numerical expression for the hysteretic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…High temperature (HT) motor systems have been extensively studied [1][2][3][4][5][6] . Motors are generally driven by a pulse-widthmodulation (PWM) inverter to control torque and rotational speed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…High temperature (HT) motor systems have been extensively studied [1][2][3][4][5][6] . Motors are generally driven by a pulse-widthmodulation (PWM) inverter to control torque and rotational speed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was important to accurately measure and simulate the magnetic hysteresis and iron loss properties. Recently, we have shown that iron loss of conventional non-oriented (NO) electrical steel sheets and amorphous magnetic materials (AMM) excited by PWM inverter decreases in tandem with an increase in temperature 4,6) . Previous studies have also shown that in NO sheets and AMM, the area of minor loops in hysteresis loops diminishes as the temperature increases 4,6) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to control the rotational torque and speed of the motor, pulse width modulation (PWM) inverters are usually used. In the recent times, several researchers have shown that the iron losses of the magnetic core under PWM inverter excitation increase due to time harmonic components [17][18][19][20][21][22][23][24][25][26][27][28][29] . Therefore, it is necessary to estimate the influence of time harmonic components in the motor with NMM to develop the low loss motor systems.…”
Section: Introductionmentioning
confidence: 99%